The implication of translanguaging on the linguistic competencies of deaf students - Olufemi Timothy Adigun; Olufemi Timothy Adigun; Mots’elisi Mathosa; Chikodi Joy Anyanwu (Frontiers in Communication)
The language competencies of the deaf students are key to various academic discourses that are associated with the learning outcome of deaf students and social interaction between deaf individuals and non-deaf members of society. Methods to assist the deaf in building appreciable language capacities have been encouraged in various studies. Hence, translanguaging has been found as a concept that could influence the linguistic repertoire of deaf students but there is a dearth of systematic review studies on the influence of translanguaging in deaf education, this study therefore provided evidence on the implication of translanguaging in the education of deaf students. Ten bibliographic databases were identified and comprehensively searched for academic papers on translanguaging in deaf education. Thirteen published articles were carefully selected for in-depth content analysis from 5,937 academic papers. The findings revealed that there is a scarcity of studies on translanguaging in deaf education in Sub-Saharan Africa. This study showed that translanguaging serves as an inclusive fulcrum in deaf education. Furthermore, findings showed that translanguaging can be delivered through a multi-modal approach and such approach can significantly improve the language capabilities of deaf students. Implications were advised for research, policies, and practices of translanguaging in deaf education.